Epidemiology of otitis media in children from developing countries: A systematic review. (June 2016) - DeAntonio, Rodrigo; Yarzabal, Juan-Pablo; Cruz, James Philip; Schmidt, Johannes E.; Kleijnen, Jos
Abstract: Objective: This systematic review examined the epidemiology of otitis media (OM) in children <6 years within 90 developing and newly industrialised countries. Methods: Literature searches (1992–2011), based on MEDLINE, EMBASE, WHO, Index Medicus, country-specific websites, conferences, and the reference lists of included studies, yielded 11, 413 records; 59 of 344 studies analysed were included in this review. Results: The majority of the identified studies provided only a single timepoint for OM. In children <6 years of age, OM prevalence was found to be 9.2% in Nigeria, 10% in Egypt, 6.7% in China, 9.2% in India, 9.1% in Iran and 5.1–7.8% in Russia. Few studies examined the etiology of OM and the antibacterial resistance. The most common bacterial pathogens were S. pneumoniae, H. influenzae and S. aureus . A high resistance to penicillin was reported in Nigeria and Turkey. Conclusions: Despite the variability between the identified studies, this review indicates that OM and its various sub-types remain a significant burden in different settings. However, the heterogeneity of studies and a general lack of reliable data made generalisation very difficult.